2015
DOI: 10.1056/nejmoa1411587
|View full text |Cite|
|
Sign up to set email alerts
|

A Randomized Trial of Intraarterial Treatment for Acute Ischemic Stroke

Abstract: In patients with acute ischemic stroke caused by a proximal intracranial occlusion of the anterior circulation, intraarterial treatment administered within 6 hours after stroke onset was effective and safe. (Funded by the Dutch Heart Foundation and others; MR CLEAN Netherlands Trial Registry number, NTR1804, and Current Controlled Trials number, ISRCTN10888758.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

113
3,717
20
114

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 5,701 publications
(4,070 citation statements)
references
References 27 publications
113
3,717
20
114
Order By: Relevance
“…Recently it was shown that intra‐arterial treatment (IAT) is highly effective in patients with acute ischemic stroke caused by a proximal intracranial arterial occlusion, and it has revolutionized stroke treatment 1, 2, 3, 4, 5, 6…”
mentioning
confidence: 99%
“…Recently it was shown that intra‐arterial treatment (IAT) is highly effective in patients with acute ischemic stroke caused by a proximal intracranial arterial occlusion, and it has revolutionized stroke treatment 1, 2, 3, 4, 5, 6…”
mentioning
confidence: 99%
“…2015). Three months after the procedure, one additional patient reached functional independence (modified Rankin scale 0–2) for every seven patients with thrombectomy.…”
Section: Resultsmentioning
confidence: 99%
“…2014; Berkhemer et al. 2015). Merely, a minority of stroke patients has access to and even fewer eventually benefit from acute stroke therapies (Adeoye et al.…”
Section: Discussionmentioning
confidence: 99%